Mood spectrum symptoms during a major depressive episode: Differences between 145 patients with bipolar disorder and 155 patients with major depressive disorder. Arguments for a dimensional approach. (31st October 2019) - Cuomo, Alessandro; Aguglia, Andrea; Aguglia, Eugenio; Bolognesi, Simone; Goracci, Arianna; Maina, Giuseppe; Mineo, Ludovico; Rucci, Paola; Sillari, Silvia; Fagiolini, Andrea
Abstract: Background: Several studies have challenged the traditional unipolar‐bipolar dichotomy in favor of a more dimensional approach. Objective: To evaluate the differences in mood spectrum between patients with bipolar disorder (BD) and major depressive disorder (MDD) during a major depressive episode (MDE). Method: Study participants were 145 patients with BD and 155 patients with MDD recruited at three University Medical Centers in Italy. All study subjects met Diagnostic and Statistical Manual of Mental Disorders (DSM) criteria for MDE and completed the Mood Spectrum‐Self‐Report‐Last Month questionnaire. Results: Patients with BD endorsed more items in the mood manic/hypomanic and energy depressive subdomains of the MOODS‐SR questionnaire. Significant differences were also found for specific depressive and manic items, which were more frequently endorsed by patients with BD. A large number of patients with BD, but also a considerable number of patients with MDD, endorsed manic items during a depressive episode. Conclusions: There are differences between BD and MDD in terms of the number and type of mood spectrum items that are endorsed during a MDE, which may help to identify patients with BD when a retrospective assessment of a history of mania or hypomania is not possible or not reliable. A high number of patients with BD and a considerable number of patients with MDD endorsed several items in the manic section of the mood, energy, and cognition domains, this confirming the centrality of mixed features in patients with mood disorders and the need for a unitary, dimensional, descriptive and dynamic approach to MDD and BD, such as the recently proposed ACE (Activity, Cognition, Energy) model.